Atherosclerotic plaque in carotid arteries as a risk marker for cardiovascular events risk in middle aged population - A. I. Ershova; A. N. Meshkov; A. D. Deev; E. L. Aleksandrova; N. E. Lishchenko; А. S. Novikova; О. V. Khoroshilova; Е. A. Shutemova; О. A. Belova; Т. V. Balakhonova; S. А. Shalnova; О. М. Drapkina; et al. (Кардиоваскулярная терапия и профилактика, 2018)
Aim. To reveal the associations of carotid arteries atherosclerosis severity and cardiovascular events in mostly middle aged population.Material and methods. In the study, 1100 persons participated of the ATHEROGEN-Ivanovo trial (substudy of ESSE-RF), age 40-67 y. o. All participants underwent duplex scan of carotid arteries (Samsung Medison MySono U6) with assessment of the number of atherosclerotic plaques (AP), maximum stenosis and total stenosis with calculation of gender-specific quintiles. With the Cox regression model, risk was estimated for combinatory endpoint including all-cause death, myocardial infarction, novel onset of coronary heart disease, stroke, any area revascularization. Median follow-up 3,8 years.Results. The AP were found in 74,5% males and 58,0% females. In males atherosclerosis was more severe: maximum stenosis 27 (0-34)% in males vs 22 (0-58)% in females (р<0,001), total stenosis — 48 (0-90)% vs 22 (0-31)% (р<0,001) and plaques number — 2 (0-3) vs 1 (0-2) (р=0,000). There were 24 endpoints documented. 23 of 24 endpoints occurred in persons with at least any ultrasound marker value within quintile ≥3. Regression showed that if at least one ultrasound marker should have reached the quintile ≥3 (e. g., maximum stenosis ≥25% in men), than the risk of events from combinational endpoint would increase 8,5 times — 95% CI 1,12-64,76 (p=0,039). Also, coronary heart disease increases the risk 4,05 times  — 95% CI 1,46-11,21 (p=0,007), acute stroke 3,49 times — 95% CI 1,19-10,23 (p=0,023). The number of males with AP <25% was 15%.Conclusion. The presence of AP in carotid arteries does 8,5 times increase the risk of cardiovascular events, and for 15% of males in population with AP in carotid arteries that narrow the lumen <25%, it is needed to clarify the risk.